(untitled) (American Journal of Multidisciplinary Research and Innovation, 2025)
This study explores the social consequences of child marriage on girls in Kolmudanga, Uttar Patary and Boldiaghat villages at Patari Union of Naogaon District, Bangladesh. In this study, we applied qualitative research methods because of study area related limitations. In this case Data were collected employing case studies, focus group discussions and document analysis. 35 respondents (31 female and 4 male) were selected by snowball sampling techniques. The findings shows that social repercussions of child marriage, including high rates of divorce, post-marital affairs and remarriage as well as impoverishment, marital rape, and family violence. Among 35 respondents the average age of marriage was 13 years (the average age of female respondent was 11 years where male 15), the lowest age of girls were 10 (four cases) and boys were14 years old (two cases). Nine cases of this study had divorce for one or more times, where five cases have remarriage which is an alarming trend in the study area. Marital rape, dowry and domestic violence are responsible for divorce in the study area. There was a relationship among divorce, post marital affairs and remarriage. High number of divorces plays in post marital affairs which often contributes to remarriage. Because of multiple divorce, romantic relationships and repeated marriage, girls are becoming stigmatized both within their families and in society, which is significantly affecting their mental and social beauty or social well-being. Child marriage poses a major obstacle to social equality at Patari union in rural Naogaon District of Bangladesh. The findings serve as valuable insight for academics and policymakers indicating the way of effective plans and program regarding effects of child marriage. Ultimately, the study makes a significant contribution to the realization of sustainable development goals (SDGs), particularly goal 5, which promotes gender equality, and goal 10, which focuses on reducing inequalities. Eliminating child marriage will help create a safer, more equitable, and promising future for Bangladeshi girls.